2022
DOI: 10.3389/fpsyg.2022.927688
|View full text |Cite
|
Sign up to set email alerts
|

Visual post-occupancy evaluation of a restorative garden using virtual reality photography: Restoration, emotions, and behavior in older and younger people

Abstract: Natural environments have a restorative effect from mental/attentional fatigue, prevent stress, and help to revitalize psychological and physical resources. These benefits are crucial for promoting active aging, which is particularly relevant given the phenomenon of population aging in recent decades. To be considered restorative, green spaces have to meet specific requirements in ecological and psychological terms that can be assessed through Post-Occupancy Evaluation (POE), a multimethod approach commonly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Specifically, the applied intervention significantly reduced the symptoms of depression by 46%, 21%, and 24% for stroke, cardiac, and pulmonary patients, respectively, suggesting that the intervention could be effective in patients with different medical conditions (Rutkowski et al 2021 ; Jóźwik et al 2021 ; Szczepańska-Gieracha et al 2021b ; Kiper et al 2022 ). Other studies using VR greenery have shown similar effectiveness (Boffi et al 2022 ): Chan et al ( 2021 ) showed that a short walk in a virtual forest improved the emotional state of the elderly; a recent mixed-method feasibility study demonstrated the usefulness of different nature-based VR environments in mood improvement (Kalantari et al 2022 ); and the use of the VR garden idea had positive effects on affect, well-being and stress in the face of isolation related to the COVID-19 pandemic (Malighetti et al 2022 ; Meyer et al 2022 ; Pallavicini et al 2022 ). Nevertheless, the main difference between the above research and this study was the additional implementation of psychotherapeutic elements in our intervention.…”
Section: Discussionmentioning
confidence: 61%
“…Specifically, the applied intervention significantly reduced the symptoms of depression by 46%, 21%, and 24% for stroke, cardiac, and pulmonary patients, respectively, suggesting that the intervention could be effective in patients with different medical conditions (Rutkowski et al 2021 ; Jóźwik et al 2021 ; Szczepańska-Gieracha et al 2021b ; Kiper et al 2022 ). Other studies using VR greenery have shown similar effectiveness (Boffi et al 2022 ): Chan et al ( 2021 ) showed that a short walk in a virtual forest improved the emotional state of the elderly; a recent mixed-method feasibility study demonstrated the usefulness of different nature-based VR environments in mood improvement (Kalantari et al 2022 ); and the use of the VR garden idea had positive effects on affect, well-being and stress in the face of isolation related to the COVID-19 pandemic (Malighetti et al 2022 ; Meyer et al 2022 ; Pallavicini et al 2022 ). Nevertheless, the main difference between the above research and this study was the additional implementation of psychotherapeutic elements in our intervention.…”
Section: Discussionmentioning
confidence: 61%
“…The current study found that VR natural experiences were found to have positive effects on individuals' mental health outcomes. Previous studies also suggested a similar result that VR natural experiences improve mental health outcomes (Boffi et al 2022;Moyle et al 2018;Veling et al 2021;. A previous randomized control trial conducted a VR nature study by watching one of six 4-min monoscopic 360° videos of natural environments on VR headsets from Monday to Saturday each week (Browning et al 2023).…”
Section: Discussionmentioning
confidence: 89%
“…Virtual parks simulate real parks with multisensory stimuli for attention and mental restoration, emotional stability, and stress recovery (Sun et al 2023). Previous experimental studies suggested that VR natural experiences across different populations could improve multiple mental health outcomes, including physiological and psychological stress indicators, affects (Allen et al 2018), relaxation, perceived restoration (Bornioli et al 2018), happiness, moods, awareness (Moyle et al 2018), emotions (Olafsdottir et al 2017), anxiety , distress, nervousness (Veling et al 2021), and depressive symptoms (Boffi et al 2022).…”
Section: Related Workmentioning
confidence: 99%
“…As a matter of fact, the APP and the exp-EIA© method were developed to specifically foster collaborative and human-centered urban design processes with an evidence-based approach. Indeed, this tool allows users to collect, analyze, and spatialize subjective reactions to specific environments, i.e., describing the intangible features of spaces through the perspective of its users; the outcomes are presented in various forms, including geolocated psychological data [52][53][54]. When applying the exp-EIA© method via City Sense, participants have to: (1) register to the app and input their socio-demographic information, for statistical and data filtering purposes; (2) fill in a brief questionnaire related to the chosen neighborhood, including a question on how familiar they are with the area on a 5-points Likert scale and a multiple choice question with multiple select answers option concerning the main reasons for frequentation (e.g., work, shopping, social relations).…”
Section: The Experiential Walk: Materials and Measuresmentioning
confidence: 99%